Social Marketing Promotion Strategy on Pregnant Women’s Decision to Adopt “Sayang Bunda” Application in Semarang, Indonesia - Tiwuk Puji Rahayu (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Semarang City’s Health Office launched “SAYANG BUNDA” android-based mobile application simultaneously, aiming to help pregnant women find out and monitor their pregnancy health, thereby can improve Antenatal Care (ANC) coverage. Purwoyoso and Ngaliyan public health centers with low visit ANC coverage and not achieving the target of program. The purpose of this study was to examine the effect of sales promotion, personal selling, advertising, and publication on pregnant women’s decision to adopt “SAYANG BUNDA” android-based mobile application.Subjects and Method: This was a case-control study conducted at Purwoyoso and Ngaliyan health centers, in Semarang City, from August to November 2019. A sample of 84 pregnant women was selected for this study. The dependent variable was pregnant women’s decision. The independent variable was social marketing promotion strategy including sales promotion, personal selling, advertising, and publication. The data were collected by questionnaire and analyzed by a multiple linear regression.Results: The result of multiple-linear regression analysis showed that sales promotion (b=0.223; SE=0.406; p=0.005) and personal selling (b=0.286; SE=0.406; p=0.000) affect strongly the introduction of pregnant women’s need and contribute by 40.6%. Sales promotion(b=0.346; SE=0.330; p=0.000), personal selling(b=0.177; SE=0.330; p=0.026), advertising and publication(b=-0.253; SE=0.330; p=0.002) affect strongly and contribute by 33% to information search. Sales promotion(b=0.214; SE=0.169; p=0.035) affects most strongly and contributes by 16.9% to alternative evaluation. There is no strong effect of sales promotion(b=0.025; SE=0.069; p=0.839), advertisingand publication(b=0.216; SE=0.068; p=0.094), and personal selling(b=0.001; SE=0.069; p=0.994) and contributes by 6.9% to trying and adopting. Advertising and publication (b=1.685; SE=0.082; p=0.037)affect most strongly and contributes by 8.2% to pregnant women’s post-use assessment.Conclusion: To improve pregnant women’s decision to adopt the “SAYANG BUNDA” android-based mobile application, Semarang City’s Health Office improves and focuses social marketing strategy on promotion mix strategy including advertising, sales promotion, publication, and personal selling.Keywords: social marketing promotion strategy, pregnant women’s decision, SAYANG BUNDA applicationCorrespondence: Tiwuk Puji Rahayu. Masters Program of Health Promotion, Universitas Diponegoro. Email: tiwp01@yahoo.co.id. Mobile: 085790337111.Journal of Health Promotion and Behavior (2020), 5(2): 104-113https://doi.org/10.26911/thejhpb.2020.05.02.05